A quality systems study of Topy Industries, Incorporated - Andrade, Elaine I.; Baligod, Robin V.; Zomil, Joanna V. (Diliman, Quezon City College of Engineering, 1996)
Topy Industries, Incorporated if a fast growing manufacturing firm specializing in the production of plastic containers. For years now, it has managed to maintain the quality level of its outgoing products acceptable to the customers they serve. The group conducting the study, hoever, found out that problems regarding quality matters are present within the company. Although the customers are generally satisfied with the products that are delivered to them, the existing quality system of Topy is not very satisfactory. Due to non-availability of data and time constraints, the documentation phase was restricted to the plant area only, covering the departments of Quality Control, Research and Development, Production and Engineering and Warehouse. Through interviews with the Quality Control supervisor, the plant manager and several machine operators, information relevant to the quality systems study was culled. In addition to these, data from inspection report forms helped in analyzing the present performance of the process and the machines. Using a quality audit questionnaire, the company was rated depending on the extent of the application of different techniques as perceived by the group. The summary of the quality audit results was used as a guide in locating the problem areas. A stream diagnostic chart further added insight into these areas of improvement. After the problem areas have been analyzed and the root causes have been recognized which turned out to be top management related, specifically, the lack of quality goals leading to the insufficient quality tools employed in production, overlapping of work responsibilities, lack of QC and R&D personnel and the absence of a preventive maintenance program. A set of recommendations is drawn up and divided into different phases that gears toward total quality management. Along with the recommendations, a two year implementation program is being proposed, ending with a quality audit, the nature of which could be a subject for further study.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 135 : Industrial Quality Control
Keywords: Topy Industries Incorporated; Plastics industry and trade; Quality control